The Impacts of Village Fund Direct Cash Assistance Distribution Implementation during the COVID-19 - Rizki Mita Utami; Dwiyanto Indiahono; Sendy Noviko (Universitas Gadjah Mada, 2023)
Direct cash assistance has often been criticized for its limited impact in the long-term community empowerment. However during the Covid-19 pandemic this method of assistance was deemed necessary to help the poor survive. This article discusses the implementation of the Village Fund Direct Cash Assistance (Bantuan Langsung Tunai-Dana Desa/BLT-DD) policy during COVID-19 pandemic in Sokawera Village, Banyumas Regency. The study aimed to determine the impacts of implementation of the BLT-DD policy in Sokawera Village. A descriptive qualitative method was selected for the study, and the research was conducted in Sokawera Village, Cilongok District, Banyumas Regency, Central Java. Study data were collected through interviews, observations, and documentation. The results showed that target groups felt appropriate benefits of the BLT-DD and are satisfied bottom-up decision making approach of the program. Based on the discussions attended by program implementers, namely village officials, village council (BPD), community unit heads (Ketua RW), neighborhood unit heads (Ketua RT) and community leaders, human resource capacity was deemed adequate to implement the policy and there was no influence of power or interests among implementers that affect policy implementation. The strategy adopted in implementing the policy is to conduct an awareness campaign and establish cooperation between the stakeholders. The study discovered several obstacles, namely the misuse of BLT-DD benefits, distribution delays, limited budget resulting in limited distribution, non-compliance of certain implementers, and the emergence of social envy among residents. The implication of this study is that the government can develop an application system that can help identify the target group correctly. In addition, the government must also ensure the availability of a budget for the poor, so that assistance can cover poor families as the overall target group.